A comparative study of production costs for enhancing safe curry paste production based on primary GMP standard: A case of community enterprises in Songkhla province - Sopin Jirakiattikul (Prince of Songkla University, 2022)
Southern Thailand curry paste is an identity food ingredient. Nowadays, its production has been scaled up to generate a supplemental income for local households. It is therefore necessary to have a production process that protects health of consumers. The objectives of this study were to determine the cost for safe curry paste production of 40 curry paste producing community enterprises in Songkhla province by the concept of cost of manufactured product. Data collection was carried out by assessing and scoring the operation at production sites based on the primary Good Manufacturing Practice (pGMP) criteria associated with interviewing the chairman and principal committees of the community enterprises. Curry paste producing groups were classified into three groups according to their level of readiness to be complied with the pGMP standard ranging from high, medium, and low. Data analysis showed that the major part of the production cost came from raw materials expense. We found that the high level group had the lowest production per unit cost due to its ability to purchase and stock raw materials in advance so as to avoid prices fluctuation and to secure the continuation of the production supply. Budget was also systematically allocated in the case of the high level group. This study reveals the limitations and potential for enhancing capacity development of each curry paste community enterprise to meet the primary standards. Noticing the cost of production of community enterprises with different basic standards leads to good management, efficient planning and cost control. In addition, creating a network of shared learning between governmental sector and community enterprises in managing production costs and product standards brings to generate income for households in the community.